A network framework for dynamic models of urban food, energy and water systems (FEWS). Issue 1 (22nd August 2017) - Zimmerman, Rae; Zhu, Quanyan; Dimitri, Carolyn
Abstract : The urban food system addressed here centers on urban food processing, distribution and consumption (including food packaging and waste disposal) and as such addresses how food moves from processing and distribution centers to points of consumption and ultimately waste disposal within cities. The Food‐Energy‐Water Systems (FEWS) Nexus extends to and through urban boundaries. Energy and water resource use are vital along these routes and are interdependent with one another and with food processing in ways that differ from those in agricultural production systems outside urban boundaries. This paper addresses how the urban food system affects the intensity of energy and water resource use and how these interdependencies can be altered by abrupt changes or extreme events. The urban food system is significantly affected by resource disruptions such as power outages, water contamination or disruption due to droughts or distribution line breakages. The system must be able to be resilient to these changes to be sustainable. FEWS flows and usage concepts presented in this paper are based on system characteristics analogous to one of the largest food distribution centers in the U.S. and the largest city, the Hunts Point Distribution Center in New York City. The Center handles a large share of the perishable food supply, involves numerous utilities that support one another, and a wide range of products, and thus provides a framework for evaluating urban FEWS relationships. In addition to direct energy for refrigeration, lighting, heating and cooling, indirect energy resources consumed by transportation systems that deliver food to Hunts Point exemplify interdependencies. Network models are used to describe scenarios for the interrelationships in the urban food system, including changes in the mix of resources due to conservation and other resource decisions as well as disruption of those resources in an extreme event. Selected food consumption and production practices are also considered. The modeling framework provides a generalizable network model that captures extreme weather event effects and enables the quantitative static and resilience analysis and planning. The extreme weather event component uses both static and dynamic formulations for resilience to portray changes in network topology and network changes over time respectively. The nodes of the network capture urban FEWS resources and the linkages between the nodes capture network characteristics. The network models that correspond to different scenarios are integrated to understand the interdependencies from processing through resource consumption as a basis to identify the patterns of interdependencies that lead to cascading failures, pinpoint nodes and links that are the weakest components of the network, and support resilience planning for the disruptive events. The analysis and design of the network will inform the planning and recovery policies to enhance the resiliency of the FEW critical infrastructures of New York City and potentially transferrable to other large urban areas and prepare them for future anticipated and unanticipated extreme events. The modeling used for the scenarios is considered generalizable to other areas and scalable to urban food systems of different sizes and configurations. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 122–131, 2018